Association Between Celiac Disease and Autism Spectrum Disorder: A Systematic Review. Issue 5 (14th May 2021) - Quan, Joshua; Panaccione, Nicola; Jeong, Jocelyn; Underwood, Fox E.; Coward, Stephanie; Windsor, Joseph W.; Ronksley, Paul E.; Gidrewicz, Dominica; deBruyn, Jennifer; Turner, Justine M.; Lebwohl, Benjamin; Kaplan, Gilaad G.; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Objective: The aim of the study was to perform a systematic review assessing the research investigating the association between celiac disease (CD) and autism spectrum disorder (ASD). Methods: A literature search of MEDLINE and EMBASE was performed without limits placed on year or language. Observational studies reporting on the occurrence of CD among patients with ASD and/or the occurrence of ASD among patients with CD were included. Study design, characteristics, diagnostic criteria for ASD and CD, and the frequency of positive cases in the studied sample were recorded. Study quality was assessed using an adapted Newcastle-Ottawa Quality Assessment Scale. Due to substantial heterogeneity between studies, a meta-analysis was not performed. Results: Of the 298 unique citations identified within our search strategy, 17 articles evaluating the association between CD and ASD were included. Of those articles, 13 observed samples of patients with ASD, and 6 observed samples of patients with CD. Overall, most studies had small sample sizes and reported no evidence for an association between the 2 conditions. However, a limited number of population-based studies of higher quality suggested a potential association between CD and ASD. Conclusions: Most studies assessing an association between CD and ASD are at risk for systematic and/or random error. A potential link has, however, been shown in a handful of high-quality studies, and, therefore, this comorbidity cannot be ruled out. Future studies should recruit larger sample sizes, include precise definitions of CD and ASD, and exclude patients with ASD on a gluten-free diet.